Analysis of the chain-mediated effects of nurses’ sense of professional gain and sense of professional mission between psychological resilience and work engagement in 10 general hospitals in Sichuan province - Liu, Zhenfan; Chen, Cui; Yan, Xiaoting; Wu, Jijun; Long, Lin (Frontiers in Psychology, 2024)
Objective To explore the chain-mediated role of sense of career benefit and sense of career mission in the mechanism of psychological flexibility's effect on nurses' work engagement.Adopting the convenience sampling method, 1032 nurses in 10 general hospitals in Sichuan Province were surveyed by questionnaires using the General Information Questionnaire, Sense of Occupational Benefit Scale, Sense of Occupational Mission Scale, Psychological Flexibility Scale, and work engagement Scale in August-October 2022, and the model of the chained-mediated effect was constructed and validated. Results The total psychological resilience score of nurses in 10 general hospitals in Sichuan Province was (91.29±17.38), the total score of sense of occupational benefit was (137.85±21.02), the total score of sense of occupational mission was (40.27±7.37), and the total score of work engagement was (34.99±9.80). The total score of nurses' work engagement was positively correlated with the total scores of psychological elasticity, sense of professional benefit, and sense of professional mission (all P<0.05). The direct effect of psychological elasticity on nurses' work engagement was significant, with an effect value of 0.321; the chain mediation effects of occupational benefit and occupational mission as separate mediators and the chain mediation effects of the two were 0.039, 0.032, and 0.062, respectively. Conclusion Nurses' work engagementin 10 general hospitals in Sichuan province is at a medium level, and occupational benefit and occupational mission play a significant role in the mechanism of the psychological elasticity's